Managerial role perception In organization - Cogill, Charles John (My University, 1981)
In this thesis, a study is made on the cognitive processes and maps by which managers, in interaction with each other, perceive and organize stimuli related to the functions which they fulfill in the organizations involved. An attempt is made to analyze and explore, via a systems approach and complementary action frame of reference, the nature, and structure of role-perceptions that top-level functional managers have of each other. These role perceptions are viewed fror:1 the the framework of middle-range organization theory. It is hypothesized that managers will simplify their perceptual worlds by reducing a large number of stimuli to a simple evaluative structure and that certain axes of differentiation, which further affects this evaluative structure, maybe identified. The hypotheses are derived from the interest of the author in the perceptual categories that managers use naturally in assessing each other, the structure of these categories, and the effects of role. In order to answer the questions posed, data was collected from 90 of the most senior functional and general managers in 10 randomly selected medium-sized South African industrial companies. The data was obtained by means of a specifically devised 10 x 40 Repertory grid (Kelly, 1955) and semi-structured interviews. Holzbach's (1974) version of French and Raven's ( 1968) bases of power instruments were used for supplementary interpretation of the data. The repertory grids of 90 managers ( 36 000 observations) were compared on a hypothetico-deductive basis against a codel quasi-consensus grid of identical dimensions, to test for the effects of perceptual mediation in terms of personal construct and implicit personality theories. Thereafter the effects of the role and organizational decision making as axes of differentiation were explored on the basis of the phenomenological viewpoint that managers have certain models, theories, or cognitive maps which affect perception and therefore behavior. (Abbreviation abstract)
A thesis submitted to the Faculty of Business Administration, University of the Witwatersrand, Johannesburg, for the Degree of Doctor of Philosophy
Keywords: Managers; Organizations; Role perceptions